E-government-enabled transparency: The effect of electoral aspects and citizen's access to Internet on information disclosure. Issue 3 (2nd July 2020) - Tejedo-Romero, Francisca; Araujo, Joaquim Filipe Ferraz Esteves
ABSTRACT: Recent literature on transparency claims that e-government-enabled transparency through websites may be conditioned by political and social factors. Being more transparent while conducting its activities and political responsibilities has been the response of governments to citizens' demand for access to public information. This paper analyzes if political and social conditions influence transparency in Portuguese municipalities. The results show that political ideology, electoral turnout, proximity of elections, citizens' access to Internet and geographic location influence municipalities' transparency. The analyses are based on panel data from all 308 Portuguese municipalities.